Effector Caspases and Leukemia - Ying Lu; Guo-Qiang Chen (International Journal of Cell Biology)
Caspases, a family of aspartate-specific cysteine proteases, play a major role in apoptosis and a variety of physiological and pathological processes. Fourteen mammalian caspases have been identified and can be divided into two groups: inflammatory caspases and apoptotic caspases. Based on the structure and function, the apoptotic caspases are further grouped into initiator/apical caspases (caspase-2, -8, -9, and -10) and effector/executioner caspases (caspase-3, -6, and -7). In this paper, we discuss what we have learned about the role of individual effector caspase in mediating both apoptotic and nonapoptotic events, with special emphasis on leukemia-specific oncoproteins in relation to effector caspases.